On some solitary wave solutions of the Estevez--Mansfield--Clarkson equation with conformable fractional derivatives in time - Ahmed Nauman; Macías-Díaz Jorge E.; Umer Shazia; Baber Muhammad Z.; Jawaz Muhammad; Vargas-Rodríguez Héctor (Open Physics)
In this study, a generalization of the Estevez–Mansfield–Clarkson (EMC) equation that considers the presence of conformable time-fractional derivatives is investigated analytically. The integer-order model finds applications in mathematical physics, optics, and the investigation of shape developing in liquid drops. In this study, the Sardar sub-equation method, is employed to solve the generalized EMC equation. From the Sardar sub-equation method a broad range of soliton solutions, including dark-bright, combined dark-singular and periodic singular solitons, have been obtained. Some of the results derived in this study are plotted to illustrate that the solutions are solitary waves, indeed.